2021
DOI: 10.47263/jasem.5(1)05
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Utaut in the Context of M-Payment Usage Intention in Malaysia

Abstract: This study revises the existing UTAUT model and incorporates two additional variables, namely trust, and convenience. In addition, the literature on the mediating effect of trust and performance expectancy in Malaysia in the context of m-payment usage intention is still limited. This study also attempts to fill the knowledge gap and examine the mediating effect of trust and performance expectancy. A total of 393 usable questionnaires were collected in Malaysia and analyzed using IBM Amos version 23. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Statistically, it was proven that effort expectancy does not have a significant effect on behavioral intention. This finding is very contradictory to previous research, which explained that effort expectancy has an effect on the use of M-Payment in Oman and Malaysia (Al-Saedi et al , 2020; Tang et al , 2021), online zakat payment in Indonesia (Kasri and Yuniar, 2021) and learning about zakat through social media (Mohd Suki et al , 2022). However, the insignificant relationship between effort expectancy is an interesting finding to be revealed further.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Statistically, it was proven that effort expectancy does not have a significant effect on behavioral intention. This finding is very contradictory to previous research, which explained that effort expectancy has an effect on the use of M-Payment in Oman and Malaysia (Al-Saedi et al , 2020; Tang et al , 2021), online zakat payment in Indonesia (Kasri and Yuniar, 2021) and learning about zakat through social media (Mohd Suki et al , 2022). However, the insignificant relationship between effort expectancy is an interesting finding to be revealed further.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, based on previous empirical research, it was found that the UTAUT construct, especially effort expectancy, performance expectancy and social influence, did not have a significant impact on individuals’ intentions to use digital services. It means that there are inconsistencies in research results (Gunawan and Novendra, 2017; Virgiyanti et al , 2018; Merhi et al , 2019; Purwanto and Loisa, 2020; Khalid et al , 2021; Kasri and Yuniar, 2021; Tang et al , 2021; Bin-Nashwan, 2022; Chopdar et al , 2022). Therefore, the second novelty shown in this study aims to test the indirect effect to obtain significant results or positioning PS as an intervening variable that mediates the relationship between effort expectancy, performance expectancy and social influence on behavioral intention.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kethineni and Yao (as cited by Koroma et al, 2022), trust is believed to have a significant role in the disruption of existing technology. According to Tang et al (2021), trust is critical in the early stages of introducing technology. Mendoza et al (2018) explained that when someone lacks trust, they will have doubts about using it.…”
Section: Trustmentioning
confidence: 99%
“…As a new type of investment asset, the government is questioning how public trust is formed so people want to invest in cryptocurrency. According to several studies, current cryptocurrencies owners' trust is influenced by the sense of security and guarantees provided by service providers, precisely crypto exchanges (Tang et al, 2021;A. Wijaya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation